Investigations on the crystalline, topographic, electrical and optical characteristics of doubly doped (Si + F) SnO2 films deposited using spray pyrolysis technique. (October 2015) - Turgut, G.; Thirumurugan, K.; Ravichandran, K.
Highlights: First report on the simultaneous doping of Si and F with SnO2 thin films deposited using spray pyrolysis technique. Relatively minimum resistivity is obtained after doping. All the results are correlated with each other. Abstract: Silicon and fluorine (Si + F) co-doped SnO2 thin films were deposited on soda lime glass substrate using the spray pyrolysis technique. The Si and F doping levels were varied from 0–10 and 2.5–10 in steps of 2.5 at. %, respectively. Initially the optimum doping level of Si is found (7.5 at. %) at which the film exhibits the minimum electrical resistivity value (4.23 × 10 −3  Ω cm) and then the doping level of F is varied and it is found to be better at 10 at. % on which it offers lower resistivity of 1.96 × 10 −4  Ω cm. From the structural studies, it is observed that the preferential orientation of all the films is along (2 1 1) plane irrespective of dopant and level of doping, but the peak intensity decreases as the doping level increases. The average transmittance of the all the films is found to be around 75% in the visible region and the optical band gap of the films are found to be in the region of 3.79–3.99 eV.